Association of transketolase polymorphisms with measures of polyneuropathy in patients with recently diagnosed diabetes. Issue 4 (15th May 2016) - Ziegler, Dan; Schleicher, Erwin; Strom, Alexander; Knebel, Birgit; Fleming, Thomas; Nawroth, Peter; Häring, Hans‐Ulrich; Papanas, Nikolaos; Szendrödi, Julia; Müssig, Karsten; Al‐Hasani, Hadi; Roden, Michael; et al.
Abstract: Background: Shunting of glycolytic intermediates into the pentose phosphate pathway has been suggested to protect from hyperglycaemia‐induced microvascular damage. We hypothesized that genetic variability in the gene encoding transketolase, a key pentose phosphate pathway enzyme, contributes to early nerve dysfunction in recent‐onset diabetes. Methods: In this cross‐sectional study, we assessed nine single nucleotide polymorphisms (SNPs) in the transketolase gene, plasma methylglyoxal concentrations, and clinical and quantitative measures of peripheral nerve function in 165 type 1 and 373 type 2 diabetic patients with a diabetes duration up to 1 year. Results: The Total Symptom Score was associated with transketolase SNPs rs7648309, rs62255988, and rs7633966, while peroneal motor nerve conduction velocity (MNCV) correlated only with rs7648309 ( P  < 0.01). Cold thermal detection threshold (TDT) (foot) was associated with transketolase SNPs rs11130362 and rs7648309, while warm TDT (hand) correlated with rs62255988 and rs7648309 ( P  < 0.01). After Bonferroni correction, the correlations of transketolase SNP rs7648309 with Total Symptom Score and rs62255988 with warm TDT (hand) remained statistically significant. Among subgroups, men with type 2 diabetes showed the strongest associations. No associations were observed between each of the nine tagged transketolase SNPs and plasma methylglyoxal concentrations. Conclusions: The observed associations of genetic variation in transketolase enzyme with neuropathic symptoms and reduced thermal sensation in recent‐onset diabetes suggest a role of pathways metabolizing glycolytic intermediates in early diabetic neuropathy. Copyright © 2016 John Wiley & Sons, Ltd.